Design optimization of offshore construction vessels - Sandvik, Endre (NTNU, 2016)
The topic of this thesis is optimization of ship design with regards to operational performance. 4 VARD Offshore Subsea Construction Vessels are analysed to find the optimum compromise of operability versus required power, building costs and machinery costs. Operability is assessed with regards to subsea lifting operations using the ShipX plugin VERES. Criteria is established for lifting phases in air, splash-zone and lowering through the water column. Parametric variations of beam, draught, GM and radius of gyration for roll motion is done to find their effect on operability. Required power at transit speed for beam and draught variations is found using experimental results from MARINTEK and the empirical method Holtrop 84. Building and machinery costs are assessed using empirical methods. Statistics from the North Sea and Norwegian Sea is applied to determine operability. Results from these areas is found to differ significantly. The only parameter resulting in consistent change in operability is the vessel length. The remaining parameters vary in terms of their effect on operability depending on vessel and operational area. The length is found to have the largest impact on costs, and the beam is found to be a more cost effective parameter for increasing operability compared to draught. It is shown that variation of beam is more difficult compared to draught if a constant GM is required without large modifications of general arrangement. The applied methodology of assessing operability differs from the procedure of planning and executing lifting operations since weather windows and -factors are neglected. This lead to an overestimate of operability represented as the expected percentage of time the vessel is capable of performing operations.